2017
DOI: 10.1002/2017gl074681
|View full text |Cite
|
Sign up to set email alerts
|

In situ observations of magnetosonic waves modulated by background plasma density

Abstract: We report in situ observations by the Van Allen Probe mission that magnetosonic (MS) waves are clearly relevant to the background plasma number density. As the satellite moved across dense and tenuous plasma alternatively, MS waves occurred only in lower density region. As the observed protons with “ring” distributions provide free energy, local linear growth rates are calculated and show that magnetosonic waves can be locally excited in tenuous plasma. With variations of the background plasma density, the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 27 publications
7
66
0
Order By: Relevance
“…The MS waves in the magnetosphere are usually excited by proton ring distributions (∂ F /∂ V ⊥ > 0) near the magnetic equator (Chen et al, ; Horne et al, ; Meredith et al, ; Xiao et al, ). They have been observed in a wide magnetospheric region ( L ~ 2–8) (Fu et al, ; Ma et al, , ; Su et al, ; Yuan et al, ; Zhima et al, ). Here we for the first time observed the MS wave amplification and attenuation associated with the magnetospheric compression and expansion.…”
Section: Introductionmentioning
confidence: 98%
“…The MS waves in the magnetosphere are usually excited by proton ring distributions (∂ F /∂ V ⊥ > 0) near the magnetic equator (Chen et al, ; Horne et al, ; Meredith et al, ; Xiao et al, ). They have been observed in a wide magnetospheric region ( L ~ 2–8) (Fu et al, ; Ma et al, , ; Su et al, ; Yuan et al, ; Zhima et al, ). Here we for the first time observed the MS wave amplification and attenuation associated with the magnetospheric compression and expansion.…”
Section: Introductionmentioning
confidence: 98%
“…Satellite observations (Boardsen et al, ; Ma et al, ; Meredith et al, ; Min et al, ; Perraut et al, ) have shown a close relation between the excitation of magnetosonic waves and a ring‐like (or partial shell) distribution of tenuous energetic protons, and theoretical calculations (Chen, ; Chen, Thorne, Jordanova, & Horne, ; Curtis & Wu, ; Gul'elmi et al, ; McClements et al, ; Min & Liu, ; Sun, Gao, Chen, et al, ; Yuan et al, ) have verified that a proton ring distribution with the ring velocity V R comparable to the Alfven speed V A provides free energy to excite magnetosonic waves. The excitation of magnetosonic waves by a proton ring distribution in a uniform magnetized plasma has been thoroughly studied using 1‐D particle‐in‐cell (PIC) simulations (Chen et al, ; Liu et al, ; Sun, Gao, Lu, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these waves were observed in the dayside low‐density plasmatrough following intense substorms (AE>500 nT), generally consistent with previous statistical studies of magnetosonic waves on the basis of low‐resolution data (Boardsen et al, ; Hrbáčková et al, ; Kim & Shprits, ; Ma et al, ; Meredith et al, ; Němec et al, ; Shprits et al, ). Magnetosonic waves can be destabilized by the substorm‐injected hot protons (Boardsen et al, ; Curtis & Wu, ; Gary et al, ; Gulelmi et al, ; Horne et al, ; Meredith et al, ; Yuan et al, , ) and propagate over a broad region (Chen & Thorne, ; Horne & Miyoshi, ; Kasahara et al, ; Ma et al, ; Němec et al, ; Santolík et al, ; Su et al, ), allowing the subsequent nonlinear wave‐wave interactions (Perraut et al, ). However, different from previous statistics (Yang et al, ), the occurrence of these unusual magnetosonic waves did not show any clear dependence on the geomagnetic storm activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the high‐resolution frequency‐time spectrograms, magnetosonic waves often appear as discrete emission lines tracking the local proton gyrofrequency harmonics (Balikhin et al, ; Gary et al, ). This characteristic can be well explained by the local Bernstein mode instability of hot proton ring distributions (Boardsen et al, ; Curtis & Wu, ; Gary et al, ; Gulelmi et al, ; Horne et al, ; Meredith et al, ; Perraut et al, ; Yuan et al, , ). Previous ray tracing simulations have suggested that magnetosonic waves are not trapped near the source region but propagate radially and azimuthally in the low‐latitude region (Chen & Thorne, ; Horne & Miyoshi, ; Horne et al, ; Kasahara et al, ; Ma et al, ; Němec et al, ; Santolík et al, ).…”
Section: Introductionmentioning
confidence: 96%